(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In today’s tight race for the top spots, a well-rounded approach to training and nutrition, including the appropriate selection of foods, timing of meals, and supplements, is essential. An athlete’s degree of athletic performance is directly influenced by their nutritional state one of the most essential dietary considerations for physically active individuals is making sure they have enough energy to do their favorite activities. Fatigue, recurrent sickness, and decreased performance are all symptoms of an energy-deficient diet and the study which discussed about Nutrition, Important of Sports Nutrition, Supplementation, and The Importance of Nutrition for Athletes, Assessment of Intake and Dietary Quality in Athletes, Are Improvements Needed, Health and Fitness, Nutrition Health Are Closely Related, Sports Foods, Factors Influencing Diet Choices of Athletes.